Inorganic carbon system dynamics in landfast Arctic sea ice during the early‐melt period. Issue 5 (19th May 2015) - Brown, Kristina A.; Miller, Lisa A.; Mundy, C. J.; Papakyriakou, Tim; Francois, Roger; Gosselin, Michel; Carnat, Gauthier; Swystun, Kyle; Tortell, Philippe D.
Abstract We present the results of a 6 week time series of carbonate system and stable isotope measurements investigating the effects of sea ice on air‐sea CO2 exchange during the early melt period in the Canadian Arctic Archipelago. Our observations revealed significant changes in sea ice and sackhole brine carbonate system parameters that were associated with increasing temperatures and the buildup of chlorophyll a in bottom ice. The warming sea‐ice column could be separated into distinct geochemical zones where biotic and abiotic processes exerted different influences on inorganic carbon and pCO2 distributions. In the bottom ice, biological carbon uptake maintained undersaturated pCO2 conditions throughout the time series, while pCO2 was supersaturated in the upper ice. Low CO2 permeability of the sea ice matrix and snow cover effectively impeded CO2 efflux to the atmosphere, despite a strong pCO2 gradient. Throughout the middle of the ice column, brine pCO2 decreased significantly with time and was tightly controlled by solubility, as sea ice temperature and in situ melt dilution increased. Once the influence of melt dilution was accounted for, both CaCO3 dissolution and seawater mixing were found to contribute alkalinity and dissolved inorganic carbon to brines, with the CaCO3 contribution driving brine pCO2 to values lower than predicted from melt‐water dilution alone. This field study reveals a dynamic carbon system within the rapidly warming sea ice, prior to snow melt. We suggest that the early spring period drives the ice column toward pCO2 undersaturation, contributing to a weak atmospheric CO2 sink as the melt period advances.